Dissipative Magnetic Soliton in a Spinor Polariton Bose–Einstein Condensate - Jia, Chunyu; Wu, Rukuan; Hu, Ying; Liu, Wu-Ming; Liang, Zhaoxin (Frontiers in Physics, 2021)
Magnetic soliton is an intriguing nonlinear topological excitation that carries magnetic charges while featuring a constant total density. So far it has only been studied in the ultracold atomic gases with the framework of the equilibrium physics, where its stable existence crucially relies on a nearly spin-isotropic, antiferromagnetic, interaction. Here, we demonstrate that magnetic soliton can appear as the exact solutions of dissipative Gross-Pitaevskii equtions in a linearly polarized spinor polariton condensate with the framework of the non-equilibrium physics, even though polariton interactions are strongly spin anisotropic. This is possible due to a dissipation enabled mechanism, where spin excitation decouples from other excitation channels as a result of gain-and-loss balance. Such unconventional magnetic soliton transcends constraints of equilibrium counterpart, as well as providing a novel kind of spin-polarized polariton soliton for potential application in opto-spintronics.